The 5E Learning Cycle Model Supported by Augmented Reality: Its Impact on Students’ Learning Outcomes and Critical Thinking Skills in Economics Education - Ayis Crusma Fradani; Dwi Nila Andriani (JURNAL EKONOMI PENDIDIKAN DAN KEWIRAUSAHAAN, 2026)
Objective: Teaching economics in vocational high schools often faces challenges such as low student achievement and limited critical thinking, largely due to conventional, less interactive methods. Innovative approaches are needed to link abstract concepts with real-world contexts. This study examines the impact of the 5E Learning Cycle model supported by Augmented Reality on students’ learning outcomes and critical thinking skills. Method: A quasi-experimental design with a pretest–posttest control group was employed, involving two 11th-grade Digital Business classes at SMK Negeri 1 Bojonegoro (34 students each). One class received the intervention, while the other served as control. Instruments included tests for learning outcomes and critical thinking, analyzed using independent samples t-test, N-Gain, and effect size (Cohen’s d). Results: Showed significant improvements in the experimental group: learning outcomes (51.94 to 79.39) and critical thinking (18.59 to 28.99), with moderate N-Gain (0.51; 0.58) and large effect sizes (0.99; 0.90). Novelty: The study’s novelty lies in applying the 5E Learning Cycle model with Augmented Reality to vocational economics education, extending its use beyond science and STEM fields.